2020
DOI: 10.1016/j.breast.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and survival outcomes in breast carcinosarcoma: A SEER population-based study

Abstract: Objectives Carcinosarcoma of the breast is a rare disease. Its clinicopathological features and prognosis are not well defined. The aim of this study was to compare the clinicopathological features and clinical outcome between breast carcinosarcoma and breast invasive ductal carcinoma (IDC). Materials and methods Patients with breast carcinosarcoma and breast IDC were identified through the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Breast cancer with unusual histological types is a kind of specific breast cancer, which were estimated in a low prevalence and consists of diverse categories with a beyond standard number according to different guidelines, and at least eighteen histological types were currently presented and remained updated with the in-depth understanding and advances in molecular pathology [ 3 ]. Previous studies have managed to discuss the clinical features and prognosis of special histological breast cancer [ [4] , [5] , [6] , [7] ]. However, most of them were studies that merely contained a limited cohort adopted in a single medical institution, of which the characteristics of clinical profiles and prognosis could be discordant, or primarily focused on a specific category of breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer with unusual histological types is a kind of specific breast cancer, which were estimated in a low prevalence and consists of diverse categories with a beyond standard number according to different guidelines, and at least eighteen histological types were currently presented and remained updated with the in-depth understanding and advances in molecular pathology [ 3 ]. Previous studies have managed to discuss the clinical features and prognosis of special histological breast cancer [ [4] , [5] , [6] , [7] ]. However, most of them were studies that merely contained a limited cohort adopted in a single medical institution, of which the characteristics of clinical profiles and prognosis could be discordant, or primarily focused on a specific category of breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Few epidemiological studies have reported on the incidence, demography, clinicopathology, and survival outcomes of PIOL. The Surveillance, Epidemiology, and End Results (SEER) database, which collects the incidence and survival information of cancer patients covering almost 28% of the population in the United States (US), provides valuable information on tumor characteristics and survival outcomes and is an especially vital resource for studies of rare cancers [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we performed propensity score matching to eliminate the confounding factors. 16 Univariate and multivariate analyses of OS and CSS in patients with T1 stage AEGJ treated with surgery and chemoradiation after propensity score matching showed that surgery could significantly lower the risk of death compared with patients who received chemoradiation alone. However, univariate and multivariate analyses of OS and CSS in patients with T1 stage AEGJ treated with surgery and surgery+chemoradiation after propensity score matching showed similar risk of death, which suggested that chemoradiation before or after surgery could not improve patients’ survival rate.…”
Section: Discussionmentioning
confidence: 98%